Refugees' integration in the Austrian labour market: Occupational mobility and job-skills mismatch - Sandra M. Leitner; Michael Landesmann (The Vienna Institute for International Economic Studies (wiiw), 2020)
wiiw publishes a detailed study on occupational mobility and job-skills mismatch of the recent wave of refugees from the Middle East (predominantly from Syria, Iraq, Afghanistan and Iran) in the Austrian labour market. The study is based on two waves of an extensive survey of refugees conducted between December 2017 and May 2019, comprising 1,600 and 2,400 respondents respectively. The following are the key findings: (i) Occupational mobility analysis suggests a steep decline in 'occupational status' when comparing the last job in the home country and the first job attained in Austria, and a slight recovery afterwards-a 'mirror J' pattern. (ii) The initial decline is particularly strong for persons with tertiary degrees, and for those who worked as professionals, senior officials and managers before leaving their home countries. (iii) Occupational trajectories of female refugees differ from those of their male counterparts in that they experience a steeper occupational downgrade between their last job in the home country and first job in Austria and there is little evidence of an occupational recovery after the initial drop. (iv) In both waves of the survey, about 60% of the respondents regard themselves as 'overqualified' in their current employment; a higher share of males than of females in this self-assessment think of themselves as 'overqualified'. The share of those who think they are 'overqualified' jumps to 70-74% among those with higher educational attainment levels.
Keywords: J15; J24; J61; J62; 330; Refugees; occupational trajectories; job-skills mismatch; Austria; refugees from MiddleEast; migrants' job-market integration